EFFECT OF COMPENSATION AND WORK ENVIRONMENT TOWARDS JOB SATISFACTION IN MEDIATION BY WORK MOTIVATION - Ramadhanti , Shafira; Hidayat, Nurdin; Dalimunthe, Sholatia (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect on compensation and work environment on job satisfaction by mediating by work motivation in employees of the Directorate of Resources of the Ministry of Education, Culture, Research and Technology. This study used quantitative methods with population of 145 employees and a sample of 106 employees of the Directorate of Resources of the Ministry of Education, Culture, Research and Technology. The model in this study is to use a path analysis model (path analysis). SEM (Structural Equation Modeling) operated with the SmartPLS version 3.0 program for hypothesis testig.